2018
DOI: 10.12973/ojcmt/2355
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Communication in Social Networking Sites: An Investigation in the Framework of Uses and Gratification Theory

Abstract: In the twenty-first century, thanks to the development of information and communication technologies that, communication possibilities between people is getting unlimited. People can reach and follow anyone as whenever they want. Especially, after the development of web 2.0 which ensures interactive communication, social media has become much dominant in people's lives. The social media is valuable for people to create social networks and sustain their relations, also protects the communication between them. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Bu anlamda, iletişim araştırmaları alanında ortaya çıkan yaklaşımlar, kitleler tarafından çokça kullanılan sosyal medya ortamlarına da uygulanmaya başlamış ve dijital medya alanında yeni bulgular literatüre kazandırılmıştır (Kaye & Johnson, 2002;Papacharissi & Mendelson, 2011;Whiting & Williams, 2013;Korhan & Ersoy, 2015;Şahoğlu, 2018;Eginli & Tas, 2018).…”
Section: Dijital Medya Ortamlarında Kullanımlar Ve Doyumlar Kuramıunclassified
“…Bu anlamda, iletişim araştırmaları alanında ortaya çıkan yaklaşımlar, kitleler tarafından çokça kullanılan sosyal medya ortamlarına da uygulanmaya başlamış ve dijital medya alanında yeni bulgular literatüre kazandırılmıştır (Kaye & Johnson, 2002;Papacharissi & Mendelson, 2011;Whiting & Williams, 2013;Korhan & Ersoy, 2015;Şahoğlu, 2018;Eginli & Tas, 2018).…”
Section: Dijital Medya Ortamlarında Kullanımlar Ve Doyumlar Kuramıunclassified
“…Uses and gratification theory aids in understanding the motives behind engaging with others on online platforms and choosing a certain type of online platform over another (Severin & Tankard, 1997). This theory has been excessively applied, especially in recent studies of internet use (Dhir, Pallesen, Torsheim, & Andreassen, 2016), delivery apps (Ray, Dhir, Bala, & Kaur, 2019), microblogs , Facebook (Hossain, Kim, & Jahan, 2019), Instagram (Madan & Kapoor, 2021), and interpersonal communications (Eginli & Tas, 2018). However, when it comes to negative online reviews, studies have not utilized the theory to understand the motivational reasons for generating or engaging negative online reviews efficiently.…”
Section: Generationmentioning
confidence: 99%
“…People use social media for entertainment and to enrich themselves. Some rely on the convenience of social media platforms to gain emotional support and recognition [9], while others are motivated by the desire to share content, connect with others, express themselves, or achieve personal goals [10]. Past studies on city promotion found that strong emotional cues [11], such as surprise or pleasure, were better at gaining public recognition.…”
Section: Literature Review 21 City-related Features and Urban Communitiesmentioning
confidence: 99%